Problem-Based Learning Approach for Elementary Schools: A case study of five Years Compulsory Education system - Hussain, Akbar Ali; Akhter, Shamim; Qureshi, Abrar Hussain; Khan, Komal (Innovation Journal of Social Sciences and Economic Review, 2021)
This study aimed to develop an effective learning model that fosters a conducive learning environment for elementary school students, with a specific focus on enhancing literacy skills through Problem-Based Learning (PBL). The research employed a mixed-methods approach, combining qualitative and quantitative analyses with research and development techniques. The study was conducted in two phases: an exploratory phase and an experimental phase. A purposive sample of 50 learners, 13 educational tutors, and six literacy program administrators participated in the study. The findings revealed that the implementation of PBL significantly improved literacy skills within an entrepreneurship literacy program. PBL was effectively integrated into the learning management system, contributing to the development of curriculum strategies, educational resources, media, and assessment methods. The study also highlighted that PBL not only enhanced students’ reading and writing abilities but also improved their problem-solving skills. In conclusion, PBL has proven to be an effective approach for enhancing literacy competencies among elementary school students. The study’s findings suggest that incorporating PBL into educational programs can create a more engaging and effective learning environment, leading to better educational outcomes. The implications of this research are significant for curriculum developers, educators, and policymakers, as it underscores the importance of adopting innovative teaching strategies like PBL to improve literacy education and overall student performance.